Epigenetic approaches to the study of macrophages in atherosclerosis - Reschen, M (2015)
Coronary artery disease (CAD) is caused by atherosclerosis, a chronic inflammatory response to modified lipoproteins. A key pathophysiological event is the lipid-induced transformation of macrophages into lipid-laden foam cells and their accumulation in atherosclerotic plaques. Heritable CAD risk is associated with common genetic variants at over 40 genomic loci; the underlying causal mechanisms remain largely unknown and could affect transcriptional regulation in foam cells. Epigenetic and gene expression changes were measured in primary human macrophages before and after exposure to atherogenic, oxidized low-density lipoprotein—with resultant foam cell formation. This unbiased approach involved open chromatin mapping with formaldehyde-assisted isolation of regulatory elements with enhancer and transcription factor mapping using chromatin immuno-precipitation. Foam cell formation was associated with changes in a subset of open chromatin and enhancer sites that were strongly correlated with expression of nearby genes. OxLDL-regulated enhancers were enriched for several transcription factors—including C/EBP-beta— that have no previously documented role in foam cell formation. OxLDL exposure up-regulated C/EBP-beta expression and increased C/EBP-beta binding across the genome, most prominently around genes involved in inflammatory response pathways. Variants at CAD-associated loci were enriched in the subset of oxLDLregulated open chromatin sites. These included rs72664324 in an oxLDL-induced super-enhancer at the PPAP2B locus. OxLDL increased C/EBP-beta binding at rs72664324. C/EBP-beta binding, enhancer activity and oxLDL-induced upregulation of PPAP2B were stronger with the protective A allele of rs72664324. The PPAP2B protein product LPP3 was expressed in foam cells in human atherosclerotic plaques and was upregulated by oxLDL exposure in macrophages, so increasing the degradation of pro-inflammatory mediators. I also found several other CAD risk candidate genes were regulated by oxLDL: Phosphatase and actin regulator 1 (PHACTR1) and macrophage inducible Ca2+ dependent C-type lectin (Mincle). This led us to find a novel expression-quantitative-trait locus for PHACTR1 in macrophages and define new glycolipid ligands for Mincle. Our results demonstrate a genetic mechanism contributing to CAD risk at the PPAP2B locus and highlight the value of integrating gene expression and epigenetic changes to study disease processes involving pathogenic environmental stimuli.